2005
DOI: 10.1073/pnas.0509402102
|View full text |Cite
|
Sign up to set email alerts
|

Activation of naïve B lymphocytes via CD81, a pathogenetic mechanism for hepatitis C virus-associated B lymphocyte disorders

Abstract: Infection with hepatitis C virus (HCV), a leading cause of chronic liver diseases, can associate with B lymphocyte proliferative disorders, such as mixed cryoglobulinemia and non-Hodgkin lymphoma. The major envelope protein of HCV (HCV-E2) binds, with high affinity CD81, a tetraspanin expressed on several cell types. Here, we show that engagement of CD81 on human B cells by a combination of HCV-E2 and an anti-CD81 mAb triggers the JNK pathway and leads to the preferential proliferation of the naïve (CD27 ؊ ) B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
197
11
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 34 publications
10
197
11
5
Order By: Relevance
“…This threshold was estimated to be up to 30 Ab molecules per virion for West Nile virus (53,54) and is represented in our model with the relation u i,j = v K j,i between the probabilities u i,j and v j,i of neutralization and immune stimulation. The neutralization effectiveness of the Ab may be further hampered by dilution with low-affinity Abs resulting from boosting of different memory B cells by a viral variant or from polyclonal antigen-independent activation of naive B cells by HCV (55).…”
Section: Discussionmentioning
confidence: 99%
“…This threshold was estimated to be up to 30 Ab molecules per virion for West Nile virus (53,54) and is represented in our model with the relation u i,j = v K j,i between the probabilities u i,j and v j,i of neutralization and immune stimulation. The neutralization effectiveness of the Ab may be further hampered by dilution with low-affinity Abs resulting from boosting of different memory B cells by a viral variant or from polyclonal antigen-independent activation of naive B cells by HCV (55).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, Ig cloned from a HCV patient with B-NHL was shown to bind to the HCV structural protein E2 (14). It also has been suggested that HCV-E2 directly activates polyclonal B cells by binding to CD81 (15). Others have proposed that direct HCV infection of B cells may cause oncogenic transformation, particularly through t(14;18) translocation (16,17).…”
mentioning
confidence: 81%
“…Mouse antihuman antibodies were used to identify immune populations as described in the literature (39,40):anti-hCD45-FITC, anti-hCD4-ECD, antihCD45RA-ECD, anti-hCD127-PE, anti-hCD25-PECy5, anti-hCD3-PECy7, anti-hCD27-PECy5, anti-hCD8-PECy7, anti-hCD31-FITC, anti-hCD19-ECD, anti-hCD16-PECy5, anti-hCD56-PE, and corresponding isotype controls (all from Beckman Coulter). Absolute number of immune subtypes was determined using Flow-Count Fluorospheres and Flow-Count method (Beckman Coulter).…”
Section: Analysis Of Immune Populationsmentioning
confidence: 99%